Religia i technonauka - Ilnicki, Rafał (Polskie Towarzystwo Religioznawcze, 2011)
Rafał Ilnicki – RELIGION AND TECHNO-SCIENCE In my article main emphasis was placed on the relation between religion and techno-science. It was problematized by showing philosophical consequences of this tendency which led to: (1) sacralization of techno-science, (2) inheriting religion functions by techno-science (discoursivity concerning radical extension of the life span, approaching eschatological subjects), (3) irrationaliza-tion of techno-science by religion and (4) merging techno-science and religion into theo-virtuality, as a form of generalized religiosity.